PENGARUH LATIHAN DEPTH JUMP OVER HURDLE TERHADAP KEMAMPUAN REBOUND BOLABASKET TIM BASKET PUTRA FIK UNJA - Hendri Munar; Usni Zamzami Hasibuan (Cerdas Sifa Pendidikan, 2018)
The purpose of this study was to obtain information about the effect of Depth Jump Over Hurdle exercise towards basketball rebound ability Men's Basketball Team in Faculty of Sport Science, Jambi University.The research method used is the Experimental method. The population of the research was 12 basketball players in the men's basketball team, FIK UNJA, and made all of the samples population called total sampling. This research instrument is vertical jump test. This research was conducted for 6 months including preparation until reporting. The study used quasi-experimental research with One-Group Pre-Test Post-Test where there was 1 independent variable and 1 dependent variable. The sample will be tested then given treatment and after that will be tested again to find out the increase in results after being given treatment. The data retrieval technique uses vertical jump test. Keywords: Basketball, Depth Jump Over Hurdle, Rebound Ability, Men’s Basketball Team FIK UNJA